Being Mentored - Garavuso Vicki (Mc Graw Hill, 2010)
In response to concerns about teacher retention, especially among teachers in their first to fourth year in the classroom, we offer future teachers a series of brief guides full of practical advice that they can refer to in both their student teaching and in their first years on the job.